Asymptotic integration of systems of integro-differential equations with degeneracies - Zavizion, G. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We construct asymptotic solutions of singularly perturbed homogeneous and heterogeneous systems of integro-differential Fredholm-type equations with degenerate matrix at the derivative.